A REFLECTION ON NON-TRANSLATION: THE CASE OF OĞUZ ATAY’S TUTUNAMAYANLAR - de PINTO, Marco Syrayama (2014)
In spite of beingrecent, no one can deny the translational momentum of Turkish authors caused bythe Nobel prize in literature, awarded to the Turkish writer Orhan Pamuk in2006. Moreover, Turkey was celebrated as the “Guest of Honor” in the 2008Frankfurt Book Fair – a fact which, as Nergis Ertürk states, clearly boostedthe number of translations from Turkish into English of 20th centuryand contemporary Turkish authors. This growing interest and the urgent to whichit testifies confronts a real paucity of scholarship in Turkish literarystudies available in English, according to the aforementioned scholar. Thepresent article aims at being a reflection on the non-translation into Englishand its possible causes of one of the most important works of 20thcentury Turkish literature, before Pamuk, in the words of Mustafa Apaydın, andwith which many other critics and scholars would agree, namely, Oğuz Atay’s Tutunamayanlar (1971-72).